Strategic priorities of Malaysian hotels: the role of management control bureaucracy - Sofiah Md. Auzair,; Amizawati Mohd Amir, (Penerbit Universiti Kebangsaan Malaysia, 2017)
The study examines the role of the management control system (MCS) in Malaysian hotels that pursue different strategic priorities. It is proposed that the cost leadership and differentiation strategies relationships to performance are indirect through the use of bureaucratic and non-bureaucratic MCSs. Data from a survey of 59 hotels operating in Malaysia were used to test the hypotheses. Using partial least squares, the results indicate no significant indirect effect of bureaucratic MCS on the relationship between cost leadership and performance. Additionally, non-bureaucratic MCS did not mediate the relationship between differentiation strategy and performance. Contrary to expectation, a significant indirect effect of bureaucratic MCS on the relationship between differentiation strategy and performance exists. The differentiators appear to affect the use of bureaucratic MCS to increase performance. The study implies the dominance of bureaucratic MCS in the Malaysian hotel industry and challenges the contingency-based proposition on the coupling of business strategy with MCS.